2017
DOI: 10.1371/journal.pone.0182981
|View full text |Cite
|
Sign up to set email alerts
|

18ß-glycyrrhetinic acid derivative promotes proliferation, migration and aquaporin-3 expression in human dermal fibroblasts

Abstract: Licorice (Glycyrrhiza) species have been widely used as a traditional medicine and a natural sweetener in foods. The 18β-glycyrrhetinic acid (18β-GA) is a bioactive compound in licorice that exhibits potential anti-cancer, anti-inflammatory, and anti-microbial activities. Many synthesized derivatives of 18β-GA have been reported to be cytotoxic and suggested for the treatment of malignant diseases. In this study, we explored the possible pharmacological roles of an 18β-GA derivative in skin biology using prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
16
1
1
Order By: Relevance
“…Glycyrrhetinic acid, on the other hand, had no significant effect in either model, which is logical in view of its differential effect on serum cytokines. However, previous in vitro studies suggested that glycyrrhetinic acid probably had anti-inflammatory properties [33, 34], which contradict our results. It is possible that the concentration of glycyrrhetinic acid used in the current study was not high enough to show its beneficial effect in in vivo animal models.…”
Section: Discussioncontrasting
confidence: 99%
“…Glycyrrhetinic acid, on the other hand, had no significant effect in either model, which is logical in view of its differential effect on serum cytokines. However, previous in vitro studies suggested that glycyrrhetinic acid probably had anti-inflammatory properties [33, 34], which contradict our results. It is possible that the concentration of glycyrrhetinic acid used in the current study was not high enough to show its beneficial effect in in vivo animal models.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, GA‐d upregulated the expression of aquaporin‐3 in fibroblasts and keratinocytes. These properties make GA a candidate for the treatment of skin diseases like wounds and dermal defects .…”
Section: Applications Of 18β‐glycyrrhetinic Acid For Skin Disordersmentioning
confidence: 99%
“…18 β -Glycyrrhetinic acid (GA, structure shown in Figure 1 ), an aglycone and active metabolite of glycyrrhizic acid, has been shown to have a series of pharmacological effects such as antioxidative [ 12 , 13 ], antitumor [ 14 16 ], and anti-inflammatory [ 17 , 18 ] activities. Moreover, in recent years, this compound has also been reported to show some protective effect in skin disorders [ 19 21 ]. However, no report has been issued on the protective effects of GA against imiquimod-induced psoriasis-like skin in vivo .…”
Section: Introductionmentioning
confidence: 99%